2000
DOI: 10.1002/1097-4598(200010)23:10<1561::aid-mus13>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of rat skeletal muscle after spinal cord transection

Abstract: We investigated the energy metabolism of the gastrocnemius muscle of the rat after spinal cord transection, using in vivo 31P magnetic resonance spectroscopy (MRS). Spectra were obtained at rest and during exercise and recovery before, and at different time‐points after, spinal cord transection. At rest, the adenosine triphosphate (ATP) level was not altered and the intracellular pH became permanently more alkaline. In electrically stimulated muscle, cord transection caused a greater phosphocreatine depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…After a cSCI, we do not observe increases in the resting inorganic phosphate content. However, similar to what is seen after a complete spinal cord transection in rats (Durozard, Gabrielle et al 2000), the trend towards an increase in the resting [Pi]/[PCr] ratios after a cSCI is accompanied with concurrent decreases in the [PCr] content. The exact mechanism of declines in [PCr] content at rest remains unknown, but is suggestive of an imbalance in the resting phosphorylation potential such that the energy available for muscle contraction and other cellular work is decreased (Taylor, Kemp et al 1993).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…After a cSCI, we do not observe increases in the resting inorganic phosphate content. However, similar to what is seen after a complete spinal cord transection in rats (Durozard, Gabrielle et al 2000), the trend towards an increase in the resting [Pi]/[PCr] ratios after a cSCI is accompanied with concurrent decreases in the [PCr] content. The exact mechanism of declines in [PCr] content at rest remains unknown, but is suggestive of an imbalance in the resting phosphorylation potential such that the energy available for muscle contraction and other cellular work is decreased (Taylor, Kemp et al 1993).…”
Section: Discussionsupporting
confidence: 77%
“…The exact mechanism of declines in [PCr] content at rest remains unknown, but is suggestive of an imbalance in the resting phosphorylation potential such that the energy available for muscle contraction and other cellular work is decreased (Taylor, Kemp et al 1993). Additionally, similar to spinal transection in rats (Durozard, Gabrielle et al 2000), we observed a slight increase in the baseline pH values; possibly indicating a shift to anaerobic metabolism after paralysis.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations